Math 417 - Section 25 Solutions
Math 417 - Section 25 Solutions
Math 417 - Section 25 Solutions
Since uxx + uyy = −6x + 6x = 0 and u(x, y) has continuous first and second partial derivatives
everywhere, u(x, y) is harmonic.
vy = ux = 2 − 3x2 + 3y 2
vx = −uy = −6xy
Differentiating the above equation with respect to x and setting the result equal to the second of
the Cauchy-Riemann equations, we get:
v(x, y) = 2y − 3x2 y + y 3 + C
y
(d) For the function u(x, y) = we have:
x2 + y 2
2
(x + y 2 )2 (2y) − 4x(2xy)(x2 + y 2 ) 6x2 y − 2y 3
2xy
ux = − uxx = − = 2
(x2 + y 2 )2 2 2
(x + y ) 4 (x + y 2 )3
x2 − y 2 (x2 + y 2 )2 (−2y) − 4y(x2 − y 2 )(x2 + y 2 ) −6x2 y + 2y 3
uy = 2 uyy = =
(x + y 2 )2 2 2
(x + y ) 4 (x2 + y 2 )3
Since uxx + uyy = 0 and u(x, y) has continuous first and second partial derivatives everywhere in
its domain (which does not include z = 0), u(x, y) is harmonic.
1
Differentiating the above equation with respect to x and setting the result equal to the second of
the Cauchy-Riemann equations, we get:
x2 − y 2 x2 − y 2
vx = 2 2 2
+ f ′ (x) = 2
(x + y ) (x + y 2 )2
f ′ (x) = 0
f (x) = C
x
v(x, y) = − +C
x2 + y 2
ux = vy , uy = −vx (1)
vx = uy , vy = −ux (2)
Taking the second of Equations (2) and substituting into the first of Equations (1) we get:
ux = vy
ux = −ux
2ux = 0
ux = 0
Therefore, u(x, y) = f (y). Similarly, by taking the first of Equations (2) and substituting into the
second of Equations (1) we get u(x, y) = g(x). In order for f (y) = g(x), it must be the case that
u(x, y) = f (y) = g(x) = C.
Since u is constant, from the Cauchy-Riemann equations we have vy = 0 and vx = 0. Thus, v(x, y) = C
as well.